The Tomato Terpene Synthase Gene Family - Abatedaga, Maria Ines de Los Angeles (2011)
Compounds of the terpenoid class play numerous roles in the interactions of plants with their environment, such as attracting pollinators and defending the plant against pests. We show here that the genome of cultivated tomato (Solanum lycopersicum) contains 44 terpene synthase (TPS) genes, including 29 that are functional or potentially functional. Of these 29 TPS genes, 26 were expressed in at least some organs or tissues of the plant. The enzymatic functions of eight of the TPS proteins were previously reported, and here we report the specific in vitro catalytic activity of 10 additional tomato terpene synthases. Many of the tomato TPS genes are found in clusters, notably on chromosomes 1, 2, 6, 8, and 10. All TPS family clades previously identified in angiosperms are also present in tomato. The largest clade of functional TPS genes found in tomato, with 12 members, is the TPS-a clade, and it appears to encode only sesquiterpene synthases, one of which is localized to the mitochondria, while the rest are likely cytosolic. A few additional sesquiterpene synthases are encoded by TPS-b clade genes. Some of the tomato sesquiterpene synthases use z,z-farnesyl diphosphate in vitro as well, or more efficiently than, the e,e- farnesyl diphosphate substrate. Genes encoding monoterpene synthases are also prevalent, and they fall into three clades: TPS-b, TPS-g, and TPS-e/f. With the exception of two enzymes involved in the synthesis of ent-kaurene, the precursor of gibberellins, no other tomato TPS genes could be demonstrated to encode diterpene synthases so far.